Відіменникові назви вмістилищ для предметів і речовин у новій українській мові кінця XVII – початку XXI століття - Сіроштан, Т.В. (Культура народов Причерноморья, 2014)
У статті розглянуто історію лексико-словотвірних типів і підтипів відіменникових назв
вмістилищ (посуду, меблів) у новій українській мові кінця ХVІІ – початку ХХІ століття, визначено
особливості мотивації та творення таких похідних, окреслено роль і місце формантів у системі
афіксальної деривації назв вмістилищ. Розв’язання цих питань дуже важливе для формування
загального уявлення про словотвірний потенціал мовної системи. Аналіз фактичного матеріалу
проведено на основі писемних пам’яток та лексикографічних джерел. В статье рассмотрено историю лексико-словообразовательных типов и подтипов
отсубстантивных названий вместилищ (посуды, мебели) в новом украинском языке конца ХVII – начала
ХХI века, определено особенности мотивации и образования таких производных, очерчено роль и место
формантов в системе аффиксальной деривации названий вместилищ. Решение этих вопросов является
очень важным для формирования общего представления о словообразовательном потенциале языковой
системы. Анализ фактического материала проведен на основе письменных памятников и
лексикографических источников. The article studies the history of the word-forming types and subtypes of substantive nominations of
receptacles (crockery, furniture) on the base of New Ukrainian language during the end of the ХVII – beginning
of the ХХI century, denotes peculiarities of motivation and formation of such derivatives, determines the role and
the place of the formants in the system of affix derivation of nominations of the receptacles. Solution of these
problems is very important to build a common understanding of word-forming potential of the language system.
The analysis was held on the basis of written records and lexical and graphic sources.
The study found that repository names (crockery, furniture) belong to the lexical and derivative category nomina
loci, which ranks a central place in the nominative system of the Ukrainian language, so as all manifestations of
human activities take place in time and space. Substantive nominations of receptacles (crockery, furniture) form
lexical and derivative group with heterogeneous composition. Derivatives with such semantics were formed by
using the suffix -ик and -ак in New Ukrainian language of the end of the ХVII century. From the beginning of the
eighteenth century their derivative activity gradually declined. Instead, suffixes -ник and -к(а) were used in this
function. The formant -к(а) had the ability to combine both the proper Ukrainian and borrowed basis. In the ХХ
century suffix -ниц(я) was activated.